Diagnóstico de salud bucodental y factores de riesgo en la Escuela sin nombre del Barrio Lindero, Escuela Río Lagartococha y Colegio Nacional Doctor Eduardo Mora Moreno de la Parroquia Chantaco, cantón Loja, año 2013. - Duque Cabrera, Ana Ivanova (2014)
There is a high prevalence of oral pathologies , the index has increased, both nationally and globally , that is related to many outstanding reasons as I mentioned regarding : economic, social , cultural and environmental , demonstrating this situation most vulnerable, high poverty ( WHO report on the global problem of oral diseases . February 2004). The objective of this research was to make the diagnosis of oral health of students in primary and secondary schools, their names should be emphasized: Nameless school ¨Rio School and National College Lagartococha ¨ Dr. Eduardo Moreno Mora¨, in the rural parish of the canton Chantaco Loja 2013. For this specific objectives as stated: To identify risk factors and determine that oral diseases are most prevalent. The results of this investigation were that 93 % had dental caries, 40% swelling of your gums, in primary teeth was found that the mesial step molar is the most prevalent with 76.9% occlusion in the permanent dentition 65 % had Angle Class I or normoclusion and 28% occlusion alterations. Of the students surveyed, 64 % brush their teeth twice a day , 62% makes a wrong technique , the frequency of consumption of cariogenic foods was 50 % consumed once a day . KEY WORDS: oral health, gingival inflammation, oral pathology, dental caries, risk factors, malocclusion, occlusal alterations.